1998
DOI: 10.1017/s0007114598001317
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of energy expenditure in free-living red deer (Cervus elaphus) with the doubly-labelled water method

Abstract: Energy expenditure was estimated using the doubly-labelled water (DLW) method in summer in five free-living adult, non-pregnant, non-lactating, red deer (Cervus elaphus) hinds (weight 107 . 3 (SE 0 . 9) kg; age 6 (SE 1) years) on lowland pasture under typical farming conditions. Climatic conditions were monitored throughout the experiment. Errors due to 2 H losses in CH 4 and faeces were calculated from previous estimates of stoichiometries. CH 4 production, fractionated water loss, urinary N and O 2 consumpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0
2

Year Published

1998
1998
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 12 publications
0
17
0
2
Order By: Relevance
“…So far DEE has been measured in eight artiodactyls (Mule deer, Odocoileus hemionus 35 ; reindeer, Rangifer tarandus 36 ; springbok, Antidorcas marsupialis 37 ; red deer, Cervus elaphus 38 ; Arabian oryx, Oryx leucoryx 13 ; sheep, Ovis aries 39 ; alpacas, Lama pacos 40 ). Comparing average DEE between these species, llamas have a DEE of 28.9 MJ/d predicted from a phylogenetic corrected regression equation for artiodactyls (FMR, MJ d −1  = 1.23 BM 0.63±0.12 , Fig.…”
Section: Discussionmentioning
confidence: 99%
“…So far DEE has been measured in eight artiodactyls (Mule deer, Odocoileus hemionus 35 ; reindeer, Rangifer tarandus 36 ; springbok, Antidorcas marsupialis 37 ; red deer, Cervus elaphus 38 ; Arabian oryx, Oryx leucoryx 13 ; sheep, Ovis aries 39 ; alpacas, Lama pacos 40 ). Comparing average DEE between these species, llamas have a DEE of 28.9 MJ/d predicted from a phylogenetic corrected regression equation for artiodactyls (FMR, MJ d −1  = 1.23 BM 0.63±0.12 , Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Using a single sample approach, they then needed only to capture the animal at the end of the measurement period for a final blood sample. Even this final sample may become redundant in some species, since Haggarty et al . (1998) measured the energy demands of Red Deer ( Cervus elephas ) by extracting water from droppings that they had observed the focal animal producing.…”
Section: Doubly Labelled Water Methodsmentioning
confidence: 99%
“…Using a single sample approach, they then needed only to capture the animal at the end of the measurement period for a final blood sample. Even this final sample may become redundant in some species, since Haggarty et al (1998) measured the energy demands of Red Deer (Cervus elephas) by extracting water from droppings that they had observed the focal animal producing. However, this completely non-invasive application of the method will not always be feasible -for example in a recent study of Meerkats (Suricata suricatta, Scantlebury et al 2002), the authors attempted to measure final isotope enrichments using urines deposited in dry sand collected immediately after production, but found them too variable to provide reliable data.…”
Section: mentioning
confidence: 99%
“…Are we really eating less, knowing that we tend to under-report food intake the more we are told we should not eat too much, or are we getting below an optimal level of physical activity for the maintenance of energy balance? Haggarty et al (1998) concluded from the data on energy expenditure in free-living red deer that energy requirements were 20 % higher than recommended intake for animals kept outdoors, and one-third higher than the value for animals kept indoors. Interestingly, the data for freeliving red deer are in the range of energy expenditure in man.…”
mentioning
confidence: 99%
“…Energy expenditure measurements are easier to perform since the development and application of the doubly-labelled water technique. The estimation of energy requirements in free-living red deer in this issue (Haggarty et al 1998) is a good example of this approach.…”
mentioning
confidence: 99%